PEMBUATAN VIDEO PROFIL DESA SEBAGAI SARANA PENGENALAN POTENSI DESA SIDOHARJO KECAMATAN PULUNG PONOROGO - -, Mun Yah Zahiroh; Nur Fitria, Rahmadrianti; Auliya, Afida; Vara Dilla, Rafidatul; Mujahidin Ma’sum, Habib; Amelia Khoirunnisa, Hana (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
A village profile video is a visual medium that presents a comprehensive picture of various aspects of life in a village. This video displays the geographical conditions, potential of natural resources, demographics, customs, and economic and social activities that characterize the town. Through interesting visualizations, the village profile video in Sidoharjo Village, Pulung District, Ponorogo Regency, aims to introduce the identity and uniqueness of Sidoharjo Village to the wider community, both at the local and national levels. In addition to introducing Sidoharjo Village to the outside environment, the Village profile video also serves as an effective promotional tool in attracting the attention of investors, tourists, and other parties interested in the development and development of Sidoharjo Village. The method used to carry out this uses the community-based action research method, which consists of stages of diagnosis, action plan, conducting research actions, conducting evaluations, and taking lessons from activities. The implementer of this community service program is the KPM 24 IAIN Ponorogo Group in collaboration with the Sidoharjo Village apparatus partners. By presenting information in an audiovisual manner, the Sidoharjo Village profile video is expected to be able to convey a message more strongly and impactfully, to encourage community and stakeholder participation in various Sidoharjo Village development programs so that it is sustainable.